Celosia argentea: Towards a Sustainable Betalain Source—A Critical Review and Future Prospects - Preekamol Klanrit; Sudarat Thanonkeo; Poramaporn Klanrit; Poramate Klanrit; Kanchanok Mueangnak; Pornthap Thanonkeo (Plants)
Betalains are nitrogen-containing, water-soluble, and non-toxic natural pigments found in various plant species. Among these, Celosia argentea (Amaranthaceae) has garnered attention as a significant source, accumulating substantial quantities of both red–purple betacyanins and yellow–orange betaxanthins. Impressively, betalain concentrations in C. argentea inflorescences can reach up to 14.91 mg/g dry weight (DW), a level comparable to that reported in red beetroot. Beyond harvesting from inflorescences, betalains can also be produced using cell culture systems, which can yield even higher amounts, up to 42.08 mg/g DW. Beyond their role as vibrant natural colorants, betalains exhibit impressive health-promoting properties, most notably potent antioxidant activities. For instance, C. argentea inflorescence extracts demonstrate approximately 84.07% 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 88.70% 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. Extracts derived from cell cultures show even higher scavenging capacities, reaching up to 99.28% for ABTS and 99.63% for DPPH, rivaling the antioxidant standard (ascorbic acid). Further research indicates additional potential benefits, including anti-inflammatory, antimicrobial, anticancer, antidiabetic, and hepatoprotective properties. This diverse bioactivity underpins their value across various industries. Betalains serve as natural colorants and functional ingredients in food and beverages, offer sustainable alternatives for textile dyeing, and hold therapeutic promise in cosmetics and pharmaceuticals. This review critically examines existing research on betalain production in C. argentea. Recognizing that research specific to C. argentea is less extensive compared with that on species such as Beta vulgaris and Hylocereus polyrhizus, this review analyzes its biosynthetic pathways, diverse biological properties, and wide-ranging applications. This is achieved by integrating available C. argentea-specific data with relevant insights drawn from these more broadly studied betalain sources. Furthermore, the review discusses perspectives on future research directions aimed at optimizing yield and exploring the full potential of betalains, specifically within C. argentea.